ANALYSIS OF LEARNING DIFFICULTIES AND STUDENT MISCONCEPTIONS IN THE USE OF SUMO DIRHAMS (SUPER MODULE AND HUMAN RIGHTS INTERACTIVE VIDEO) IN HUMAN RIGHTS COURSES - Rarasati, Ida Putri; Baihaqi, M. Iqbal (Transpublika Publisher, 2022)
This study aims to find out the obstacles that cause learning difficulties and misconceptions faced by students of the Balitar Islamic University, especially in Pancasila and Citizenship Education Study Program on human rights courses. The research method used is descriptive analysis using tests and questionnaires which are expected to be able to find out the causes of learning difficulties and student misconceptions in human rights courses. The findings revealed that the greatest percentage of difficulty is found in internal factors which include difficulties in determining data analysis techniques with a percentage of 81,25% and difficulties in conducting data analysis with a percentage of 93,75%. While learning difficulties from external factors are known to have the highest percentage of difficulties adapting to the dynamics of society at 81,25%. From the results of interviews with students who experience misconceptions, it shows that students are still confused about the selection of data analysis techniques from observations and research results in the community. This is because the data obtained in the community are very diverse in form and data must be analyzed or triangulated, so that conclusions can be determined that are intact and interrelated.